Properties of Composite Resins Early After Curing: Color Stability, Degree of Conversion, and Dimensional Stability - Sahar Amirinejad; Narges Panahandeh; Hassan Torabzadeh (International Journal of Dentistry)
Conclusion: Time of exposure to coffee after curing had a significant effect on the color stability of X-tra fil only. X-tra fil showed minimum dimensional changes after 1 month.